2015
DOI: 10.1002/elps.201500315
|View full text |Cite
|
Sign up to set email alerts
|

Improving the sensitivity in chiral capillary electrophoresis

Abstract: CE is known for being one of the most powerful analytical techniques when performing enantioseparations due to its numerous advantages such as excellent separation efficiency and extremely low solvents and reagents consumption, all of them derived from the capillary small dimensions. Moreover, it is worth highlighting that unlike in chromatographic techniques, in CE the chiral selector is generally within the separation medium instead of being attached to the separation column which makes the method optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 91 publications
0
15
1
Order By: Relevance
“…The SEFs for d ‐ and l ‐Leu peaks were 2970 and 2400, respectively. To our knowledge, the obtained SEFs were higher than those in the previous reports on the MCE analysis of chiral compounds . As shown in Fig.…”
Section: Resultscontrasting
confidence: 61%
“…The SEFs for d ‐ and l ‐Leu peaks were 2970 and 2400, respectively. To our knowledge, the obtained SEFs were higher than those in the previous reports on the MCE analysis of chiral compounds . As shown in Fig.…”
Section: Resultscontrasting
confidence: 61%
“…Sanchez‐Lopez et al. reported in their review article that Ma et al. used field‐amplified sample stacking coupled with matrix removal by electroosmotic flow pump, and the authors found a sensitivity enhancement up to 3000 times in chiral analysis when compared to hydrodynamically injected β ‐blockers .…”
Section: Resultsmentioning
confidence: 99%
“…CE is an effective technique for stereoisomer analysis due to the high separation efficiency. This is also reflected in the number of recent reviews published on CE enantioseparations . The scope of chiral CE‐MS as well as the application of nonaqueous CE in chiral analysis have been addressed.…”
Section: Separation and Analysis Of Small Moleculesmentioning
confidence: 99%